KARAKTERISTIK KARKAS SAPI PERANAKAN SIMMENTAL JANTAN DI RUMAH POTONG HEWAN KOTA SEMARANG Carcass Characteristics of Simmental Crossbreed Cattle Slaughtered at Semarang City Slaughterhouse - Ridwan, M.H. Ridwan; Arifin, M. Arifin; Purbowati, E. Purbowati (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2018)
This study aims to assess and characterize the products of slaughter (carcass) Simmental bull crossbreed cattle slaughtered in the Slaughter House Semarang in March to April 2016. The material is used as the object is 60 Simmental bull crossbreed catlle were slaughtered in RPH Semarang, the catlles are selected by looking at the characteristics Simmental bull crossbreed cattle is white on the forehead, with a horn in black and yellow, have nail color and tail hair of black, yellow, and white, and has a body color of brown and red brick. The variables were observed in this study were age, slaughter weight, carcass weight, carcass percentage, as well as the quality grade. The results showed that the average Simmental bull crossbreed catlle were slaughtered in slaughterhouses Semarang own age 3 ± 0.60 years, slaughter weight 572 ± 130.85 kg, carcass weight 312 ± 66.00 kg, carcass percentage 51.5 ± 1.25%, and quality grade choice. Conclusion the results of the study are cattle crossbreed Simmental were slaughtered in slaughterhouses Penggaron Semarang still less optimum (age 3 years,slaughter weight 572 kg, carcass weight 312 kg, carcass percentage 51.5%, and quality grade choice) and still has the potential for improved productivity in terms of both quantity and quality, and thus the expected productivity of cattle crossbreed Simmental in Indonesia can be increased so as to support efforts to increase the productivity of national beef catlle.Keywords: Simmental crossbreed cattle, carcass, quality grade.